Evaluation of MAGLUMI syphilis test for accurate detection of syphilis antibodies in blood donors and suspected syphilis cases - Wei Fang; Yun Zhang; Min Shi; Yuqin Liao; Lanhuan Peng; Hailin Zhong; Jun Yin; Taoran Mo; Heng Li; Zhonggang Fang (Frontiers in Cellular and Infection Microbiology)
BackgroundThe diagnosis of syphilis is critical to initiate treatment at an early stage and control the syphilis epidemic. The serological detection of treponemal antibodies is recommended in the reverse sequence screening algorithm as the first screening test.Study designSerum samples from 5,081 unselected blood donors and 213 hospitalized patients were collected to evaluate the diagnostic specificity. To assess the diagnostic sensitivity, 487 positive samples were collected. 405 cross-interference samples were tested to evaluate analytical specificity. All samples were tested with the MAGLUMI Syphilis (Chemiluminescence immunoassay, CLIA) Test and the obtained results were compared with the Abbott ARCHITECT Syphilis TP reference test.ResultsThe diagnostic specificity and sensitivity of the MAGLUMI Syphilis (CLIA) Test was 99.96% (95% CI, 99.87-99.99%) and 100.00% (95% CI, 99.22-100.00%), respectively. The analytical specificity and the analytical sensitivity of the Test was 100.00% and 2.529 mIU/ml, respectively. No significant interference and cross-reactivity were observed in a number of potential factors.ConclusionsThe performance of the MAGLUMI Syphilis (CLIA) Test makes it suited for identification of treponemal antibodies in screening populations as well as patients presenting with suspicion of syphilitic infection.